Development of non-arbitrary to the arbitrary iconic words in Javanese language - Sunarya; Sumarlam; Widodo, Sahid Teguh; Sri Marmanto (Penerbit Universiti Kebangsaan Malaysia, 2017)
Onomatopoeic words in Javanese language are an evidence of the uniqueness of both the lingual aspects and the described facts. This study discussed the phenomenon of phonological and morphological language processing. It examined the derivation of the onomatopoeic root words of Javanese language into some form of the word as iconic formation. The data source covers the source language of local print media and another complementary source which was obtained from informants living in the regions of Surakarta and Yogyakarta. This study revealed the Ullman’s onomatopoeic classification of primary and secondary onomatopoeias. The primary onomatopoeic is sound imitations of referents, i.e. crowing, roaring, barking sounds, etc. The secondary onomatopoeia is the sound which arises beyond the occurring acoustic experience; they are sounds produced by movements and physical, and mental quality of an object. i.e. the word bruk (voice of falling heavy objects), prang (sound of a broken plate). The development of sound imitation icon as an icon causes a shift in the status of a root word form or onomatopoeic sound imitator to other states. Words like thuthuk [ṭuṭU?] ‘'beater', kethuk kempyang [kəәṭU? kəәmpjaŋ] 'typical instrument used in Gamelan', pethuk [pəәṭU?] 'coming across' and bathuk [baṭU?] 'forehead' were the derivative words which originated from the root word thuk [ṭuk] with the additional formative process, repetition on the root word, compounding, and reduplication. In the Javanese language, onomatopoeic words often have the same family with other words.